Elaboração de uma história em quadrinhos utilizando tópicos de Física para o ensino médio - Lorençon, Bruno Darros (2019)
In this work we present the elaboration of a comic book as a complementary material for the Physics teacher, whose plot takes place in an amusement park, where the characters experience situations in which some specific physical concepts are worked through the story. Subjects were chosen on Newtonian mechanics, thermodynamics, optics in mirrors and the double-slit experiment. The educational product resulting from this master's degree was applied to students of the three high school series of a State School, located in the state of São Paulo. The application of the developed material was performed after the theoretical presentation of the physical contents involved in the respective classroom of the High School serving as an introduction to the Comics. One of the main objectives of this work is, through play, to encourage students to read in order to improve motivation and the study of science in Basic Education, such as Physics. The purpose is to increase students' interest for more elaborate readings of the concepts worked. To collect a feedback from learners about their overall satisfaction with our approach we performed the verification of the frequency with which the students read didactic books or other literary genres and also if the genre worked, approaching concepts of Physics, was to the liking of the same ones. Those were done through a questionnaire and discussions during the application of the material. The discussions were recorded in audio. The material analyzed suggests that there was a greater understanding of the concepts of Physics using the Comics, which also contributed to improve the interaction among students in the classroom making the environment more pleasant and motivating for the treatment of Physics classes. The educational product developed has the format of a comic book containing the explanation of all the respective concepts of Physics addressed in the situations experienced by the characters of the story, being written in a language accessible to all Physics teachers of High School.